THE IMPORTANCE AND PERFORMANCE ANALYSIS OF SERVICE QUALITY OF BLUE BIRD TAXI IN MANADO - Pakiding, Tri Wahyuni R.B. (Sam Ratulangi University, 2016)
The research aims to analyze the Importance and Performance of Service Quality of Blue Bird Taxi in Manado. This research uses Descriptive Quantitative method. 100 people of Blue Bird Taxi were surveyed as the respondents. The result shows 6 attributes are plotted in quadrant I which are Important by customers but the Performance is not good enough. There are 5 attributes that are plotted in quadrant II which are Important and the Performance are as good as the expectations. There are 7 attributes in quadrant III which are not important and the performance also not good. And the last, there are 2 attributes that are plotted in quadrant IV which are not so important by customers but the Performance is good.